EXTRAFLORAL NECTARIES IN THE TROPICAL TREE GUAREA-MACROPHYLLA (MELIACEAE) - Morellato, LPC; Oliveira, P. S. (Natl Research Council Canada, 1994)
This paper describes the anatomy and morphology of the complex nectary systems of the tropical tree Guarea macrophylla Vahl (Meliaceae) and presents the first record of extrafloral nectaries occurring on reproductive organs (fruits) of a member of the order Sapindales. The extrafloral nectaries of G. macrophylla occur on petioles, petiolules, the abaxial surface of all leaflets, leaf buds, and over the surface of fruits. All extrafloral nectaries are distinctly raised above the surface. Foraging ants collect extrafloral nectar on Guarea trees both day and night. We suggest that the presence of extrafloral nectaries might be a useful taxonomic character for the identification of Guarea species.
Keywords: GUAREA; MELIACEAE; EXTRAFLORAL NECTARIES; ANTS